Infrared imaging of trauma patients for detection of acute compartment syndrome of the leg - Katz, Laurence M; Nauriyal, Varidhi; Nagaraj, Shruti; Finch, Alex; Pearlstein, Kevin; Szymanowski, Adam; Sproule, Charles; Rich, Preston B; Guenther, B D; Pearlstein, Robert D (Critical care medicine, 2008)
Early compartment syndrome is difficult to diagnose, and a delay in the diagnosis can result in amputation or death. Our objective was to explore the potential of infrared imaging, a portable and noninvasive technology, for detecting compartment syndrome in the legs of patients with multiple trauma. We hypothesized that development of compartment syndrome is associated with a reduction in surface temperature in the involved leg and that the temperature reduction can be detected by infrared imaging. Observational clinical study. Level I trauma center between July 2006 and July 2007. Trauma patients presenting to the emergency department. Average temperature of the anterior surface of the proximal and distal region of each leg was measured in the emergency department with a radiometrically calibrated, 320 x 240, uncooled microbolometer infrared camera. The difference in surface temperature between the thigh and foot regions (thigh-foot index) of the legs in trauma patients was determined by investigators blinded to injury pattern using thermographic image analysis software. The diagnosis of compartment syndrome was made intraoperatively. Thermographic images from 164 patients were analyzed. Eleven patients developed compartment syndrome, and four of those patients had bilateral compartment syndrome. Legs that developed compartment syndrome had a greater difference in proximal vs. distal surface temperature (8.80 +/- 2.05 degrees C) vs. legs without compartment syndrome (1.22 +/- 0.88 degrees C) (analysis of variance p < .01). Patients who developed unilateral compartment syndrome had a greater proximal vs. distal temperature difference in the leg with (8.57 +/- 2.37 degrees C) vs. the contralateral leg without (1.80 +/- 1.60 degrees C) development of compartment syndrome (analysis of variance p < .01). Infrared imaging detected a difference in surface temperature between the proximal and distal leg of patients who developed compartment syndrome. This technology holds promise as a supportive tool for the early detection of acute compartment syndrome in trauma patients.